Focal Salmonellosis in a Diabetic Male Involving the Soft Tissue of Anterior Chest Wall from Pakistan - Rao Muhammad Abid Khan; Muhammad Irfan; Muhammad Faisal; Ali Nadeem; Kulsoom Kazmi; Muhammad Imran (Pakistan Journal of Medical Research, 2024)
Typhoid fever remains prevalent in Pakistan, with Salmonella Typhi, the causative bacterium, known to occasionally trigger uncommon extra-intestinal ailments. The identification of a focal Salmonella infection poses a frequent challenge. This case report details an instance of an extensively drug-resistant Salmonella infection affecting the soft tissue in the anterior chest wall, effectively managed with antibiotic treatment. Our emphasis is on recognizing the importance of considering focal Salmonella infection as part of the differential diagnosis when confronted with a chronic abscess of unknown origin.